On the Female Narrative in The Canterbury Tales from the Perspective of New Historicism - Liu, Qiuyi; Huang, Chi (International Journal of Social Sciences and Public Administration, 2024)
New Historicism emphasizes the interplay between history and text, proposing an interpretation of literary works that focuses on the "textuality of history" and the "historicity of text." This paper, adopting a New Historicist approach, delves into the interpretation of female figures in The Canterbury Tales. Chaucer employs a framework-like structural form, depicting in fragmented textual fashion, whether on a large or small scale, the diverse life situations of women within the medieval context. In the New Historicist perspective , the design of female characters not only literarily reflects history but also facilitates the shaping of historical culture. It reveals the contradictions and harmonies between history and text, accomplishing the interaction between literature and history.